Monograph Series on Sustainable and Inclusive Transport - United Nations (United Nations, 2017)
This study report presents the process of development a tool for assessment and evaluation of sustainable urban transport systems in cities in the Asia-Pacific region. The report explains and illustrates how the Sustainable Urban Transport Index (SUTI) was developed. It outlines the development of a conceptual framework based on existing literature and policies on sustainable development and transport, including the Sustainable Development Goals. The report illustrates the process of identification, review and selection of indicators related to urban transport. It also elaborates the ways to normalize the indicators, weigh and calculate the elements of index. The conceptual framework, process of selection of indicators and development of the index was reviewed by two group of experts who attended the expert and regional meeting in Kathmandu and Jakarta. The sustainable urban transport index (SUTI) is based on ten indicators representing, transport system, social, economic, and environmental dimensions of sustainable urban transport. SUTI can describe key aspects of sustainable urban transport for Asian cites and help summarize, track and compare the performance of Asian cities with regard to sustainable urban transport systems and services. The report also include description of ten indicators with regards to relevance, definitions, measurement units, range of empirical values for normalization, and data sources. Based on SUTI analysis a city can consider policies and measure to improve urban transport system. It is expected that SUTI could be a useful tool for cities to assess the achievement of the related Sustainable Development Goals (SDGs), more specifically target 11.2. As part of SUTI an Excel SUTI data sheet has been developed for analysis. Entering data for all ten indicators will calculate SUTI, generate a spider diagram and allow a review of the city’s overall state of urban transport as well as performance against each indicator.